Performance of potato (Solanum tuberosum L.) genotypes under hill zone of Karnataka. - Lavanya, K.S.; Srinivasa, V.; Devaraju, D.; Lakshmana, D.; Shahid, A.; Kadian, M.S.; Archana, R.; Nandini, K.S. (2017)
An experiment was conducted to study the performance of nine genotypes of potato under hill zone of Karnataka. Among nine genotypes, maximum tuber sprout percentage was observed in Kufri Jyoti (100) followed by TT7011 (98.75) and least percentage was in C-28 (89.16). Kufri Jyoti performed better for most of the characters such as plant height(68.04 cm), number of leaves(42.21), leaf area (154.88 cm2), tuber weight (116.42 g), tuber length (8.20 cm), tuber diameter (5.88 cm), chlorophyll content (1.26 mg/g) and which was found to be significantly superior over other genotypes. Number of tubers per plant (4.43), total tuber yield per plot (18.98 kg), total tuber yield per hectare (26.36 t), marketable yield per plot (10.21 kg), marketable yield per hectare (14.18 t), dry matter (19.88 %), total sugars (2.55 %) was observed in genotype TT7011 compared to the rest of the genotypes. The genotype C-28 recorded highest starch content (24.10 %) followed by TT7007 (22.92 %) and the least starch content (19.05 %) was observed in MCIP-9-1. Genotype TT7011 realized maximum gross returns (283600.00 per ha) and net returns (193457.00 per ha) followed by TT7010 (Gross returns 190200.00 per ha and net returns 100057.00 per ha).